Feasibility and safety of cavotricuspid isthmus ablation using exclusive intracardiac echocardiography guidance: a proof-of-concept, observational trial - Debreceni, Dorottya; Janosi, Kristof-Ferenc; Turcsan, Marton; Toth, Daniel; Bocz, Botond; Simor, Tamas; Kupo, Peter (Frontiers in Cardiovascular Medicine, 2023)
Introduction Catheter ablation is the preferred treatment for typical atrial flutter (AFl), but it can be challenging due to anatomical abnormalities. The use of 3D electroanatomical mapping systems (EAMS) has reduced fluoroscopy exposure during AFl ablation. Intracardiac echocardiography (ICE) has also shown benefits in reducing radiation exposure during AFl ablation. However, there is a lack of evidence on the feasibility of ICE-guided, zero-fluoroscopy AFl ablation without the use of EAMS. Methods In this prospective study, we enrolled 80 patients with CTI-dependent AFl. The first 40 patients underwent standard fluoroscopy + ICE-guided ablation (Standard ICE group), while the other 40 patients underwent zero-fluoroscopy ablation using only ICE (Zero ICE group). Procedure outcomes, including acute success, procedure time, fluoroscopy time, radiation dose, and complications, were compared between the groups. Results The acute success rate was 100% in both groups. Out of the 40 cases, the zero-fluoroscopy strategy was successfully implemented in 39 cases (97.5%) in the Zero ICE group. There were no significant differences in procedure time [55.5 (46.5; 66.8) min vs. 51.5 (44.0; 65.5), p = 0.50] and puncture to first ablation time [18 (13.5; 23) min vs. 19 (15; 23.5) min, p = 0.50] between the groups. The Zero ICE group had significantly lower fluoroscopy time [57 (36.3; 90) sec vs. 0 (0; 0) sec, p < 0.001] and dose [3.17 (2.27; 5.63) mGy vs. 0 (0; 0) mGy, p < 0.001] compared to the Standard ICE group. Total ablation time was longer in the Standard ICE group [597 (447; 908) sec vs. 430 (260; 750), p = 0.02], but total ablation energy [22,458 (14,836; 31,116) Ws vs. 17,043 (10,533; 29,302) Ws, p = 0.10] did not differ significantly. First-pass bidirectional conduction block of the CTI and acute reconnection rates were similar between the groups. No complications or recurrences were observed during the follow-up period. Conclusion Our study suggests that zero-fluoroscopy CTI ablation guided solely by ICE for AFl is feasible and safe. Further investigation is warranted for broader validation.